Self-esteem and wellbeing among tribal and non-tribal adolescent girls - Ranjan, Lokesh Kumar; Gupta, Pramod R.; Gujar, Nilesh Maruti (International Journal of Research in Medical Sciences, 2021)
Background: Adolescent period reports experiences of changes in physical, mental and social functions. Self-esteem has a significant contribution to wellbeing and depression in adolescent. The aim and objective was to evaluate self-esteem and wellbeing among adolescent girls with tribal and non-tribal ethnicity. Methods: The cross-sectional study was conducted in which 2 schools and 1 institute selected using purposive sampling. The total enumeration method of random sampling was obtained to select participants. Total of 360 adolescent girls (180 each tribal and non-tribal adolescent girls) were selected for the study. Socio-demographic datasheet, adolescent wellbeing scale and Rosenberg self-esteem scale were used for the assessment. Results: The adolescent girls with tribal ethnicity found to have low self-esteem and wellbeing (depressive) compared to adolescent girls with non-tribal ethnicity. 33.9% of tribal adolescent girls and 13.3% of non-tribal adolescent girls found in depressive dimension. Conclusions: The deliberate efforts to build self-esteem and wellbeing among tribal adolescent girls can help to promote their mental health. The mental health promotion and wellness programs specific to ethnicity and culture requires to uphold the wellbeing of the adolescent girls with tribal ethnicity.